Pegvisomant therapy in acromegalic patient resistant to other treatment: case report - Emilia Nowicka; Michał Obel; Piotr Dzikowski; Martyna Stefaniak; Zofia Pietrzak; Ewa Obel (Kazimierz Wielki University, 2022)
Introduction: Acromegaly is a chronic, rare disorder resulting from growth hormone (GH) hypersecretion, usually caused by a pituitary adenoma. GH stimulates synthesis of insulin-like growth factor 1 (IGF-1), whom assay should be used as a screening test whenever acromegaly is suspected. Patients with acromegaly normally take from 5 to 10 years to receive a correct diagnosis, leading to complications such as cardiovascuar, respiratory, and endocrine problems that are responsible for an increase mortality. Late diagnosis of the disease also impact the effectiveness of surgical, pharmacological and radiotherapy treatment.    Case report: A 33-year-old acromegalic man with pituitary macroadenoma resistant to therapy of somastatin analogue (octreotide, lanreotide) and dopamine agonist (cabergoline). The patient underwent transsphenoidal adenomectomy, after wich high level of GH and IGF-1 were still measured. Due to the lack of the effect of the current treatment, the patient was qualified for pegvisomant therapy, as a result of which biochemical control was achieved without adverse events and with a good compliance of treatment.    Conclusions: Treatment with pegvisomant is now an important therapeutic strategy to achieve full disease control in acromegalic patients resistant or poorly responders to first generation somatostatin receptor ligands and in patients who do not respond adequately to selective excision of pituitary adenoma and /or for whom surgery is not possible.